A new technology for reducing anastomotic fistula in the neck after esophageal cancer surgery - Song, Ya-Nan; Qi, Yu; Zhang, Chun-Yang; Sheng, Yin-Liang; Wu, Kai; Zhu, Sen-Lin; Han, Lu; Shan, Ting-ting; Ye, Guan-Chao; Zhang, Qing-Yi; Chen, Yan-Li; Chen, Jin-Wei; et al. (Journal of Thoracic Disease, 2019)
Background: To explore the risk factors and prevention methods of cervical mechanical anastomotic fistula and stenosis after the radical resection of esophageal cancer. Methods: From March 2018 to November 2018, 128 patients undergoing mechanical anastomosis of esophageal cancer were selected from the Department of Thoracic Surgery of The First Affiliated Hospital of Zhengzhou University. All the enrolled patients were operated on using the Mckeown method, and a retrospective study was conducted. Data for preoperative and postoperative test indices, intraoperative embedding materials, postoperative complications, and preoperative and postoperative treatment were collected, and the relationship between various factors and the incidence of cervical anastomotic fistula and stenosis was analysed. Univariate analysis was conducted using t tests or Fisher’s exact probability method, and multivariate analysis was conducted using logistic regression models. Results: All 128 patients successfully underwent surgery without dying. The enrolled patients were evaluated using the Stooler classification, with 28 patients having grade 0, 41 patients having grade 1, 34 patients having grade 2, 21 patients having grade 3, and 4 patients having grade 4 stenosis. Patients with stenosis of grade 3 or above had obvious choking sensation, which could only be relieved by balloon dilation. Symptoms in all patients with stenosis were relieved by balloon dilation. There were no significant differences between the two groups regarding embedding materials, preoperative choking history, history of alcohol consumption, history of hypertension, history of coronary heart disease, history of diabetes, postoperative calcium concentration, average albumin concentration, average platelet concentration, body mass index, anastomotic fistula, preoperative chemotherapy, postoperative chemotherapy, or postoperative cough (P>0.05). There were significant differences in postoperative reflux (χ2=11.338, P